Karakteristik Keluarga Terhadap Kejadian Stunting Pada Anak Sekolah Dasar di Kecamatan Nanggalo Kota Padang - Oktariyani Dasril (Poltekkes Kemenkes Padang, 2019)
Stunting is a state of the body that is very short beyond the -2 SD deficit below the median (WHO, 2013). Report of the Padang City Health Office in 2017, where the incidence of stunting at the Lapai Public Health Center was 17.7%. The purpose of this study is to look at the family characteristics of stunting in elementary school children in Nanggalo District, Padang City. This type of analytic research with cross sectional design. The population of all first grade students in five public and private elementary schools is 124 people. While sampling uses a total sampling technique. Data collection on students was measured height (TB), the mother was interviewed about family characteristics related to nutritional status (level of education, economic status and parenting in the family) using a questionnaire guide. The study was conducted in May - September 2019. Data were analyzed univariately and bivariately using computerization. The results showed that 25% of respondents stunted, 19.4% had low maternal education, 24.2% had low family economic status and 48.4% of children had poor parenting. There is a relationship between family characteristics, namely the level of education (p=0,000), economic status (p=0,000) and parenting (p=0,007) with the incidence of stunting in Elementary School Children in Nanggalo District, Padang City. It is recommended that parents and health workers to improve nutritional status and reduce the incidence of stunting in children.